The way we ask for money: the emergence and institutionalization of grant writing practices in academia - Serrano-Velarde, Kathia (Minerva, 2018)
Although existing scholarship offers critical insights into the working mechanisms of project-based research funding, little is known about the actual practice of writing grant proposals. Our study seeks to add a longitudinal dimension to the ongoing debate on the implications of competitive research funding by focusing on the incremental adjustment of the funder/fundee relationship around a common discursive practice that consists in describing and evaluating research projects: How has the perception of what constitutes a legitimate funding claim changed over time and why? By investigating the normative framework enacted in the justification strategies of applicants, we shed light on the historical coevolution of the increasing competition for project funding, the epistemic culture of applicants, and grant writing rhetoric. To do this, we mobilize a comprehensive data set consisting of archival data from Europe’s oldest and largest funding agency, the Deutsche Forschungsgemeinschaft, as well as a corpus of 80 successful grant proposals written between 1975 and 2005. We find that the 1990s mark an important normative consolidation of what we consider to be a legitimate funding claim: Ensuring the success of the project and the project’s results becomes a major concern in applicant rhetoric. This time period coincides with a substantive rise in the level of competition for project funding. Yet, even though justification strategies might seem to address the same issues in grant proposals across the disciplines under investigation, the normative framework to which applicants refer differs according to the applicant’s epistemic culture.
Published online: 30 January 2018
Gesehen am 28.06.2018